Answer:
the answer is letter D
Step-by-step explanation:
the more she sleeps the higher her test score
It Wil be 73 U will have to put it ❤
Given the function
. The above function can be written as
![f(x)=3x^2-18x+23\\ f(x)=3(x^2-6x)+23\\ f(x)=3(x^2-6x+9-9)+23\\ f(x)=3(x-3)^2-27+23\\ f(x)=3(x-3)^2-4](https://tex.z-dn.net/?f=%20f%28x%29%3D3x%5E2-18x%2B23%5C%5C%20f%28x%29%3D3%28x%5E2-6x%29%2B23%5C%5C%20f%28x%29%3D3%28x%5E2-6x%2B9-9%29%2B23%5C%5C%20f%28x%29%3D3%28x-3%29%5E2-27%2B23%5C%5C%20f%28x%29%3D3%28x-3%29%5E2-4%20)
a)Now, the function
has minimum value since the coefficient of
is
.
b) The minimum value of the function occurs at
and its value is
![f(3)=3(3-3)^2-4 =-4](https://tex.z-dn.net/?f=%20f%283%29%3D3%283-3%29%5E2-4%20%3D-4%20)
c)The minimum value of the function occurs at
.
Answer:
B. 51.7699^2
Step-by-step explanation:
Last 2 wrong because it is positive.
101.... is not the definite integral for the curve
51... purrfecto
Answer:
The distributive property is not properly applied to the second polynomial.
Step-by-step explanation:
For whatever reason, it is a common mistake to say that ...
-(a +b +c) = -a +b +c . . . . WRONG!
Rather, it should be ...
-(a +b +c) = -a -b -c . . . . CORRECT